EBITDA vs. cash flows in bankruptcy prediction on the Polish capital market - Welc Jacek (European Financial and Accounting Journal, 2017)
One of the elements of company's evaluation is an analysis of bankruptcy risk metrics. In this study, the accuracy of bankruptcy predictions generated by EBITDA-based and cash flow-based liabilities-coverage ratios is evaluated within a sample of data from the Polish market. The study is based on a sample of 92 companies, in which case a bankruptcy filing was announced in a period between the beginning of 2009 and the end of the first half of 2016. The statistical analysis has confirmed the usefulness of the investigated liabilities-coverage ratios. Even though the sample covers wide variety of businesses, the logit models with only one ratio used as an explanatory variable are capable of identifying bankrupt firms (with one-period-ahead forecast horizon) in about 66-76% of cases. However, this research has not confirmed the supremacy of operating cash flows over EBITDA in predicting financial distress.
Keywords: G32; G33; 650; Ratio analysis; Bankruptcy prediction; EBITDA; Fundamental analysis; Operating cash flows